Hubungan antara stres dan pola siklus menstruasi pada mahasiswa Kepaniteraan Klinik Madya (co-assistant) di RSUP Prof. Dr. R. D. Kandou Manado - Tombokan, Kevin C.; Pangemanan, Damajanty H.C.; Engka, Joice N.A. (eBiomedik, 2017)
Abstract: Menstruation is one of the aspects of sexual maturity which occurs at the end stage of puberty in a woman. Stress entangles the neuroendocrinological system that might further affect the menstrual cycle pattern. The most common type of stress experienced by students is academical stress. This study was aimed to determine the correlation between stress and menstrual cycle pattern among pre-clinical medical students (co-assistant) at Prof. Dr. R. D. Kandou Hospital Manado. This was an observational analytical study with a cross-sectional design. There were 34 respondents obtained by using purposive sampling technique. Stress degree was assessed by using modified Depression, Anxiety, and Stress Scales 42 (DASS-42) questionnaire meanwhile the menstrual cycle pattern was assessed by using an ordinal-scaled questionnaire. Data were analyzed with the Spearman Rank Correlation test. The correlation between stress and the menstrual cycle pattern showed a p-value = 0.014 and an r = 0.417. Conclusion: There was a moderate significant correlation between stress and menstrual cycle pattern among pre-clinical medical students (co-assistant) ar Prof. Dr. R. D. Kandou Hospital Manado.Keywords: stress, menstrual cycle patterns, co-assistantÂ Abstrak: Menstruasi merupakan salah satu aspek kematangan seksual yang pertama kali terjadi pada masa pubertas seorang wanita. Stres melibatkan sistem neuroendokrinologi sehingga dapat memengaruhi pola siklus menstruasi. Stres yang paling umum dialami oleh mahasiswa ialah stres akademik. Penelitian ini bertujuan untuk mengetahui hubungan antara stres dan pola siklus menstruasi pada mahasiswa Kepaniteraan Klinik Madya (co-assistant) di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Terdapat 34 responden yang diperoleh dengan teknik purposive sampling. Derajat stres dinilai menggunakan kuesioner Depression, Anxiety, and Stress Scales 42 (DASS-42) termodifikasi dan pola siklus menstruasi dinilai dengan kuesioner yang menggunakan skala ordinal. Data penelitian dianalisis dengan uji Spearman Rank Correlation. Hasil uji korelasi antara stres dan pola siklus menstruasi mendapatkan p=0,014 dan r=0,417. Simpulan: Terdapat hubungan moderat yang bermakna antara stres dan pola siklus menstruasi pada mahasiswa Kepaniteraan Klinik Madya (co-assistant) di RSUP Prof. Dr. R. D. Kandou Manado.Kata kunci: stres, pola siklus menstruasi, mahasiswa (co-assistant)